2013
DOI: 10.4161/tisb.25718
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct epithelial tight junctions and barrier function

Abstract: Bile ducts play a crucial role in the formation and secretion of bile as well as excretion of circulating xenobiotic substances. In addition to its secretory and excretory functions, bile duct epithelium plays an important role in the formation of a barrier to the diffusion of toxic substances from bile into the hepatic interstitial tissue. Disruption of barrier function and toxic injury to liver cells appear to be involved in the pathogenesis of a variety of liver diseases such as primary sclerosing cholangit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 99 publications
1
33
0
Order By: Relevance
“…Furthermore, SOX17 also downregulated the expression of some genes involved in proliferation and inhibited the anchorage-independent growth and the invasion/migration capacity of CCA cells; this fact was associated with downregulation of different proinvasive/migration genes including S100A4 , which is a key driver for CCA dissemination [24]. The analysis of the biliary phenotype in CCA cells revealed that SOX17 stimulates the expression of the biliary marker CK7 and epithelial markers FN and ZO-1 , whose deficiency has been related to cancer progression [25]. Moreover, SOX17 normalizes the upregulated CK19 expression in CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SOX17 also downregulated the expression of some genes involved in proliferation and inhibited the anchorage-independent growth and the invasion/migration capacity of CCA cells; this fact was associated with downregulation of different proinvasive/migration genes including S100A4 , which is a key driver for CCA dissemination [24]. The analysis of the biliary phenotype in CCA cells revealed that SOX17 stimulates the expression of the biliary marker CK7 and epithelial markers FN and ZO-1 , whose deficiency has been related to cancer progression [25]. Moreover, SOX17 normalizes the upregulated CK19 expression in CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of function of TJ proteins is not lethal and the clinical manifestation is variable including very mild symptoms 102. A comprehensive description of TJ protein alterations in biliary diseases is reviewed in ref 97.…”
Section: Tj Proteins and The Gi Tractmentioning
confidence: 99%
“…It is likely that alterations of bile ducts occur through mechanosensation and consequent Ca 2+ /cyclic adenosine monophosphate signaling, rather than due to purely physical effects of increased biliary fluid pressure. Other signaling pathways stimulated by BS cause actin and tight junction remodeling that may explain the leakiness of the biliary tree …”
Section: The Role Of Intraluminal Biliary Pressurementioning
confidence: 99%
“…Other signaling pathways stimulated by BS cause actin and tight junction remodeling that may explain the leakiness of the biliary tree. (28,29,59,60) If biliary pressure plays a role, this will be most relevant for extrahepatic obstruction and PSC, anatomically characterized by bile duct dilatation and beading of the biliary tree. However, despite the evolution of knowledge on possible control mechanisms, a molecular link between either biliary pressure or bile constituents in cholestasis on the periductular cytoskeleton and associated transporter functions has not yet been demonstrated.…”
Section: > < >mentioning
confidence: 99%